Antimicrobial activity of propolis extract fractions against Staphylococcus spp. Isolated from goat mastitis - Dos Santos, Heidy C.; Vieira, Dielson S. [UNESP]; Yamamoto, Sandra M.; Costa, Mateus M.; Sá, Maria C.A.; Silva, Eva M.S.; Silva, Tania M.S. (FapUNIFESP (SciELO), 2019)
The indiscriminate use of antibiotics in the treatment of caprine mastitis causes the appearance of resistant microorganisms, besides leaving residues in milk, putting at risk to human health. In this way, propolis is an alternative in the treatment of diseases because it has antimicrobial activity, mainly because of the presence of flavonoids in its composition. The aim of this study was to evaluate the antimicrobial potential of propolis to Staphylococcus spp. Isolated from cases of goat mastitis and qualify the crude ethanoic extract by high performance liquid chromatography (HPLC). In this study, the minimum bactericidal concentration values of propolis extracts in ethanol, ethyl acetate and hexane showed that the best concentrations capable of promoting the highest mortality of the isolates of Staphylococcus spp. from mastitis in goats, were 6250, 3125 and 1562.5μg/mL, respectively. By the microplate adherence test, it was found that 20.78% isolates were not able to form biofilm, 14.70% were classified as moderate and 64.70% were weak and none as a strong biofilm producer. Propolis in its different diluents was able to affect the formation of biofilm and showed a pronounced marked antimicrobial activity against Staphylococcus spp. strains and may be indicated for use in in vivo studies.
Atividade antimicrobiana de frações do extrato de própolis frente à Staphylococcus spp. isolados de mastite caprina
Keywords: Antimicrobial activity; Caprine; Goat mastitis; Isolated; Mastitis; Propolis extract; Solvents; Staphylococcus spp